Pengaruh Kas, Bonus SWBI (Sertifikat Wadiah Bank Indonesia), Marjin Keuntungan, dan Dana Pihak Ketiga terhadap Pembiayaan Murabahah (Studi Empiris Pada Bank Umum Syariah di Indonesia) - Octaviana, Kristia; Darma, Emile Satia (Universitas Muhammadiyah Yogyakarta, Indonesia, 2012)
The paper tries to the factors which bring influence toward murabahah financing. Methods used in this research is to use Linear Regression models with SPSS software in statistical time series (time series) from January 2008-December 2010 on Sharia Public Banks. From the analysis conducted by the preparation is obtained that the independent variable (cash, SWBI bonus, profit margin, and third party fund) jointly was able to influence the dependent variable that is murabahah financing. Partially, SWBI bonus, profit margin, and third party fund affect murabahah financing, while the cash variable has no effect to murabahah financing. This is presumably because the amount of cash available to Islamic banks does not affect the amount of financing murabahah to the public. Cash in the amount greater or less did not affect Islamic banks in the dissemination of Islamic banks to the public, by way of channeling funds remain apart in the form of murabahah financing.